Intimate Partner Abuse and Child Health - Tushar Bharati; Astghik Mavisakalyan; Loan Vu (Global Labor Organization (GLO), 2024)
Despite the harmful effects of intimate partner abuse (IPA) on child health, survivors with children often continue in abusive relationships. It is often, they claim, to ensure a better future for their children. We explore the puzzle and this potential explanation using rich, longitudinal data from Australia. We show that IPA has large, long-lasting negative effects on children's health. These findings stay robust across several identification techniques, including instrumental variables, sequential difference-in-differences, and event studies. The effects seem to be driven by worsening physical and mental health of the parents, which also adversely impacts their risk-taking behavior, decrease in parents' confidence in their parenting, decrease in warm parenting, and increase in angry parenting. Finally, comparing event study graphs reveal that children of parents who separate after IPA events are no better off than children of parents who do not separate after IPA events, weakly supporting the popular explanation.
Keywords: J12; J13; 330; domestic abuse; child health; divorce